Foraminoplastic transfacet epidural endoscopic approach for removal of intraforaminal disc herniation at the L5-S1 level - Kubaszewski, Łukasz (Termedia Publishing House, 2014)
Transforaminal endoscopic disc removal in the L5-S1 motion segment of the lumbar spine creates a technical challenge due to anatomical reasons and individual variability. The majority of surgeons prefer a posterior classical or minimally invasive approach. There is only one foraminoplastic modification of the technique in the literature so far. In this paper we present a new technique with a foraminoplastic transfacet approach that may be suitable in older patients with advanced degenerative disease of the spine.